Effect of different artificial diets on biological parameters of female Chrysoperla carnea under laboratory conditions - Murtaza, Ghulam; Ramzan, Muhammad; Sultan, Yaqoob; Saleem, Fahad; Rafique, Muhammad Arsalan; Sajid, Shahmeer; Jamil, Muhammad (Journal of Scientific Agriculture, 2020)
Chrysoperla carnea (Neuroptera: Chrysopidae) is considered as a cosmopolitan polyphagous generalist predator. Chrysoperla carnea can be used in biological control programs. The biological parameters of Chrysoperla carnea were studied to check the effect different diets under laboratory conditions. The results indicate that preoviposition, oviposition and post oviposition periods were 8.2±1.25, 30.6±1.72 and 9.4±1.02 days, respectively. The highest mortalities were occurred reared at Water+ Sugar+ Yeast+ Evion diets while no mortality was observed at H2O + Sugar +Yeast + Honey. The female longevity was 51.2 ± 2.18 days. The fecundity of female was 301.31 eggs per female with 10.36 eggs per day per single female on artificial diet, H2O + Sugar +Yeast + Honey. The study revealed that H2O + Sugar +Yeast + Honey was showed highest survival and fecundity while Water+ Sugar+ Yeast+ Evion least one.